Pengembangan Video Animasi tentang Manfaat Sekolah untuk Siswa Sekolah Dasar - Rofa Darojatin Putri; Tasha Adinda Aulia; Yoga Cahya Firmansyah; Alika Fitara Dwi Permana; Rana Gustian Nugraha (Journal on Education, 2024)
Awareness of the importance of school is a challenge for the present generation. Knowledge of the benefits of school is one thing that every student should know. Therefore, this research aims to develop animated videos of school benefits to enhance the knowledge of students about school benefits. At the stage of video design this animation was made using the renderforest website continued with the addition of audio using the capcut application. The type of research used is R&D (Research and Development) with its development model ADDIE, data collection technique of media expert validation test and student response test. An animated video that has been developed by the researchers tested practiced at the Elementary School. The result of this study is that the animated video was declared “valid” based on an average rating with a presentation of 85.3% with the criterion “very qualified”, after the validity test was subsequently tested practiced in three categories namely the individual test with the presentation of 94% with the highly qualified criteria, the small group trial with the Presentation of 93.44% with the very qualified Criterion, the large group trials with the presentation of 90.15% with very qualifying criteria. Based on practical tests that have been conducted, these animated videos will be more effective if used by students individually than in groups. The results of the research showed that the development of this animated video is very worthy to be applied in the process of improving the education of students.